The Influence Of Leadership On The Performance Of Nurses In Inpatient Departments In Hospitals: Literature Review - Suci, Amin; Dioso, Regidor III (International Journal of Health Sciences, 2025)
Introduction: Good human resources can be managed with good leaders. Leaders also have the ability to motivate someone to achieve goals. Motivating nurses to carry out nursing actions is the right of the head of the room with nurses to implement a patient safety culture. In an effort to improve the performance of nurses in the inpatient department of the hospital, further research and development of leadership development programs that are appropriate to the context and specific needs in the health care environment are needed. To find out the influence of leadership on the performance of inpatient nurses in hospitals. Material and Methods: The approach used in this article is literature review. Overall, good leadership in the inpatient ward has a significant impact on nurse performance. Leaders who are able to create a positive work environment, provide support, coaching, effective communication, fair decision-making, and pay attention to nurse welfare will improve nurse performance and improve the quality of service in the hospital inpatient ward. Results: In the inpatient ward, good and effective leadership has a significant influence on nurse performance. Motivation, support, coaching, development, effective communication, fair decision-making, and meeting nurse needs are some important aspects of leadership that can improve nurse performance in the inpatient ward. Conclusion: Leaders who are able to create a positive work environment, provide support, and pay attention to nurse needs will help improve the quality of service provided and patient satisfaction.